2022
DOI: 10.7759/cureus.30919
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Psychedelic-Assisted Therapy in Managing Post-traumatic Stress Disorder (PTSD): A New Frontier?

Abstract: Post-traumatic stress disorder (PTSD) is a significant public health concern for which existing therapies are only marginally effective. Indisputably, the primary line of treatment for PTSD is psychotherapy, according to current treatment guidelines. However, PTSD continues to be a chronic condition even after psychotherapy, with high psychiatric and medical illness rates. There is a dire need to search for new compounds and approaches for managing PTSD. The usage of psychedelic substances is a potential new m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In addition, naltrexone can be highly effective in reducing alcohol intake as well as combating non-suicidal self-injury and binge eating (200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210). Other novel approaches to consider, especially when treatment-refractory major depression is a focus, may include the use of newer psychopharmacologic agents, e.g., 5-HT4 receptor antagonists (211), combining other previously unused evidence-based psychotherapies and psychopharmacologic approaches (142, 212), adjunctive application of neuromodulation tools, such as repetitive transcranial magnetic stimulation (rTMS) (213, 214), deep TMS (215) or electroconvulsive therapy (ECT) (216), novel psychotropic-or psychedelic-assisted therapies, such as ketamine/esketamine, 3,4-methylenedioxymethamphetamine (MDMA), psilocybin, and ayahuasca (12,28,212,(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229)(230)(231), as well as deep brain stimulation (DBS) (232-235), although many of these newer approaches continue to be preliminary, experimental and/or challenging to acquire.…”
Section: Nutritional Rehabilitationmentioning
confidence: 99%
“…In addition, naltrexone can be highly effective in reducing alcohol intake as well as combating non-suicidal self-injury and binge eating (200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210). Other novel approaches to consider, especially when treatment-refractory major depression is a focus, may include the use of newer psychopharmacologic agents, e.g., 5-HT4 receptor antagonists (211), combining other previously unused evidence-based psychotherapies and psychopharmacologic approaches (142, 212), adjunctive application of neuromodulation tools, such as repetitive transcranial magnetic stimulation (rTMS) (213, 214), deep TMS (215) or electroconvulsive therapy (ECT) (216), novel psychotropic-or psychedelic-assisted therapies, such as ketamine/esketamine, 3,4-methylenedioxymethamphetamine (MDMA), psilocybin, and ayahuasca (12,28,212,(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229)(230)(231), as well as deep brain stimulation (DBS) (232-235), although many of these newer approaches continue to be preliminary, experimental and/or challenging to acquire.…”
Section: Nutritional Rehabilitationmentioning
confidence: 99%
“…While large-scale clinical trials to evaluate the safety and efficacy of cannabis use are lacking (Tibbo et al, 2021), a systematic review showed that cannabis and synthetic cannabinoids may have a role in the treatment of PTSD. Similarly, prior research has demonstrated that psychedelic-assisted therapy can benefit people who experienced trauma (Mohamed, Touheed, Ahmed, Hor, & Fatima, 2022). To our knowledge, only one study has focused on using psychedelics in PTSD treatment for first responders.…”
Section: Discussionmentioning
confidence: 99%
“…Zarzutem wobec stosowania substancji psychodelicznych w leczeniu zaburzeń psychicznych, w tym PTSD, jest ich potencjalna neurotoksyczność i zwiększone ryzyko późniejszego nadużywania substancji podawanych w trakcie terapii. Lecz biorąc pod uwagę rosnące zainteresowanie badawcze tym kierunkiem leczenia, wynikające z obiecujących wstępnych wyników, niewątpliwie terapia PTSD wspomagana psychodelikami stanowi obszar wymagający pogłębionej analizy [78].…”
Section: Substancje Psychodeliczne W Leczeniu Ptsdunclassified